PENGARUH KUALITAS PELAYANAN OJEK ONLINE TERHADAP LOYALITAS KONSUMEN DI MASA PANDEMI COVID-19 DI KOTA METRO - Afifah, Pipit (LPPM STAI DARUSSALAM LAMPUNG, 2022)
Ojek Online has become one of the businesses that are currently being excellent. The business engaged in transportation services has provided many changes in community activities to be fast and efficient. However, since Indonesia was hit by the COVID-19 virus, there have been regulations from the government, namely physical distancing. This has become a challenge for online motorcycle taxi companies and has caused online motorcycle taxi service operations to be deserted from customers. Therefore, every company tries to provide the best possible service, to maintain market share. This study aims to determine the effect of online motorcycle taxi service quality on customer loyalty during the covid-19 pandemic. The method used in this research is simple regression analysis. The data of this study used a questionnaire distributed in the Metro city area. Researchers found that the quality of online motorcycle taxi services during the COVID-19 pandemic had a significant positive impact on customer loyalty.